(untitled) (International Seven Journal of Multidisciplinary, 2022)
This study examines the evolution of the professional profile of security guards in Brazil, focusing on competencies required and challenges arising from technological, organizational and regulatory changes, assuming that the profession is undergoing a reconfiguration in which the combination of technical-operational knowledge, socioemotional skills and attention to occupational health becomes central to effective performance, the investigation integrated empirical evidence on training, working conditions and institutional arrangements, identified heterogeneity in training provision, gaps in occupational health programs and ambivalences in relations between the private sector and police forces, the results point to the need for modular curricula, certification mechanisms with practical assessments and policies that articulate regulation, training and worker protection, it is recommended to implement continuous qualification programs, ergonomic measures and psychosocial support, as well as the consolidation of interface protocols between companies and public bodies, in summary, an integrated agenda is proposed to promote professionalization, legal certainty and social valorization of the security guard category in the contemporary Brazilian context.